2006
DOI: 10.1128/jvi.80.7.3147-3156.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Repression of Internal Ribosome Entry Site Activity by Double-Stranded RNA-Binding Protein 76

Abstract: Translation of picornavirus plus-strand RNA genomes occurs via internal ribosomal entry at highly structured 5 untranslated regions. In addition to canonical translation factors, translation rate is likely influenced by supplementary host and viral trans-acting factors. We previously reported that insertion of a heterologous human rhinovirus type 2 internal ribosomal entry site (IRES) into the poliovirus (PV) genome, generating the chimeric virus PV-RIPO, selectively abrogates viral translation and propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 47 publications
5
95
0
Order By: Relevance
“…This correlates well with the developmental problems found in the brains of Apaf-1 knockout mice (Cecconi et al 1998). In contrast, the IRES of HRV is repressed in neuronal cells because of the presence of the mRNA binding protein DRBP76/NF90 (Merrill et al 2006). A list of IRESes that are regulated can be found in the review by Komar and Hatzoglou (2005).…”
Section: Functional Classesmentioning
confidence: 59%
“…This correlates well with the developmental problems found in the brains of Apaf-1 knockout mice (Cecconi et al 1998). In contrast, the IRES of HRV is repressed in neuronal cells because of the presence of the mRNA binding protein DRBP76/NF90 (Merrill et al 2006). A list of IRESes that are regulated can be found in the review by Komar and Hatzoglou (2005).…”
Section: Functional Classesmentioning
confidence: 59%
“…A possible explanation is that the HeLa cells are of human origin and these splice variants have been derived from the rat. Earlier studies have specified cell type differences in IRES-regulating factors (40). As this study was carried out in RIE-1 cells using splice variants derived from the same cell type, the ODC IRES may be in a more physiologically relevant context.…”
Section: Discussionmentioning
confidence: 99%
“…NF90 was shown to inhibit replication of a broad range of viruses and to form complexes with NF45 and shuttle between the nucleus and cytoplasm (13)(14)(15)(16)(17)(18)(19). However, a detailed mechanism describing how NF90 negatively regulates virus replication remains unclear.…”
Section: Nf90 Is a Component Of Stress Granulesmentioning
confidence: 99%
“…It suppresses the function of Ebola virus polymerases through interaction with VP35 (14), inhibits HIV replication through interaction with HIV-1 TAR RNA (15,16), represses internal ribosome entry sites in rhinoviruses (17,18) and negatively regulates influenza virus replication through interaction with viral nucleoprotein (NP) (19). However, other studies (20)(21)(22)(23) found that NF90 is required for the replication of some positivestranded RNA viruses and is important for expression of E6 protein in human papillomavirus-infected cells.…”
mentioning
confidence: 96%